Investigations on oxygen limitations of adherent cells growing on macroporous microcarriers - Preissmann, A. (Kluwer Academic Publishers, 1997)
Macroporous microcarriers are commonly applied to fixed and fluidized bed bioreactors for the cultivation of stringent adherent cells. Several investigations showed that these carriers are advantageous in respect to a large surface area (Griffiths, 1990; Looby, 1990a). When growing a rC-127 cell line on Cytoline 2 (Pharmacia Biotech), no satisfactory product yield could be achieved. A possible limitation in the supply of nutrient components was investigated to explain these poor results. No significant concentration gradients could be detected. Nevertheless, fluorescence staining revealed a decreasing viability, particularly inside the macroporous structure. Therefore, oxygen transfer to and into the carriers was examined by means of an oxygen microprobe during the entire process. Additional mathematical modeling supported these results. The maximum penetration depth of oxygen was determined to be 300 μm. A critical value influencing the oxygen uptake rate of the rC-127 cells occured at a dissolved oxygen concentration of 8% of air saturation. A significant mass transfer resistance within a laminar boundary film at the surface of the carrier could be detected. This boundary layer had a depth of 170 μm. The results showed that even a 40% air saturation in the bulk liquid could not provide an efficient oxygenation of the surface biofilm during the exponential growth phase. Fluorescent staining reveals a poor viability of cells growing inside the carrier volume. Thus, oxygen supply limits the growth of rC-127 cells on macroporous microcarriers. Poor process performance and low product yield could be explained this way.